Analisis Faktor-Faktor yang Mempengaruhi Permintaan Salak di Pasar Anyar Bogor - Salsabila, Hanum; Falisha, Siti Nayla; Sajati, Shadida Syadza; Amaliasari, Nuralfi; Amanda, Della; Sitepu, Rasidin Karo Karo (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to identify and analyze the factors influencing the demand for salak fruit at Pasar Anyar, Bogor City. The observed fluctuations in demand reflect the influence of various factors, particularly economic and social aspects. Using a quantitative approach, this research employs descriptive methods and multiple linear regression analysis to examine the roles of price and income variables in influencing salak demand. Primary data were collected through questionnaires distributed to 35 respondents using an accidental sampling technique, while secondary data were obtained from relevant institutions. The results indicate that the price of salak has a negative and significant effect on demand, whereas consumer income does not have a meaningful influence. The coefficient of determination (R²) value of 66.5% suggests that the majority of the variation in demand can be explained by these two variables. These findings highlight the importance of appropriate pricing strategies in maintaining demand stability and encouraging increased purchases of salak fruit in traditional markets. Therefore, this research is expected to serve as a reference for traders and market managers in formulating more effective and responsive marketing strategies aligned with consumer dynamics.